Diversidade e zonação do Ictioplâncton em um perfil da Plataforma Maranhense - COSTA, Delzenira Silva do Nascimento da (2017)
This present work was realized out in a profile of the coastal and marine zone of the continental shelf of Maranhão (MCS). This order to describe the existence of structure patterns of fish larvae species in the coastal and marine zone of the MCS, testing the hypothesis that the community structure is related to the environmental conditions of the region. The sampling was performed and distributed at seven collection points (MA1, MA2, MA3, MA4, MA5, MA6 and MA7), throughout nine campaigns in the months of April, August, October and November 2013; January, March, May, July and September 2014. The ichthyoplankton was obtained by horizontal trawls on the surface, using a conical – cylinder plankton net with mesh of 300 μm and 60 cm of mouth diameter. The variables “temperature”, “salinity”, “conductivity”, total dissolved solids – TDS, Water transparency, dissolved oxygen, suspended particulate matter, dissolved nutrients (phosphate and nitrite) were obtained on the water surface at all collection points. The canonical correspondence analysis (CCA) was used to verify the influence of environmental variables on larval abundance and distribution. During the sample period, 4.011 fish larvae were collected, belonging to 23 families, 40 genera and 31 species. The most abundant were Anchovilla lepidentostole, Cynoscion acoupa, Sardinella brasiliensis e Mugil sp. The diversity and richness of species occurred in a way that, at the point MA1 was strongly influenced by many individuals and few species with a high degree of dominance, while in the MA7 was recorded the greatest diversity and richness of species. The more parsimonious CCA model constructed by the forward selection considered the variables water transparency (M), SPM, salinity, TSD and conductivity sufficient to explain the abundance distributions of the species. All together, these variables accounted for 89.6% of the total abundance variation in the larval species. These analyzes demonstrated the existence of two distinct sets of species, namely: i) a set of coastal species with estuarine influence; Ii) a set of marine species with oceanic influence. In general, the formation of fish larvae in the coastal and marine environments of MCS was influenced by the environmental variables of this region. The formation of these sets showed that in the MCS there is a diverse ichthyofauna of commercial and ecological importance. This indicates this area as a zone in need of conservation, in which its characteristics must be preserved.